Rest tremor correlates with reduced contralateral striatal dopamine transporter binding in Parkinson's disease. (April 2021) - Fois, Alessandro F; Chang, Florence CF; Barnett, Robert; London, Kevin; Mahant, Neil; Ha, Ainhi; Aldaajani, Zakiyah; Cruse, Belinda; Morales-Briceno, Hugo; Ma, Kit Kwan; Farlow, David; Fung, Victor SC
Abstract: Introduction: In vivo dopamine transporter imaging is a useful tool for distinguishing nigrostriatal pathologies (e.g. Parkinson's disease) from other causes of tremor. However, while many of the motoric features of Parkinson's disease (e.g. bradykinesia, rigidity, hypomimia) correlate well with reduced striatal dopamine transporter binding, the same relationship has not been demonstrated for tremor. We investigated the relationship between striatal dopamine transporter binding and quantitative measures of tremor. Methods: 23 participants with Parkinson's disease underwent standardised clinical assessment including structured, videotaped clinical examination, tremor neurophysiology study of both upper limbs using accelerometry and surface EMG, and Technitium-99 m TRODAT-1 brain SPECT imaging. Normalised striatal uptake values were calculated. Tremor EMG and accelerometry time series were processed with Fourier transformation to identify peak tremor power within a window of 3–10Hz and to calculate the tremor stability index (TSI). Results: Spearman correlation analyses revealed an association between tremor power and contralaterally reduced striatal uptake in a number of recording conditions. This association was strongest for rest tremor, followed by postural tremor, with the weakest association observed for kinetic tremor. Lower TSI was also associated with lower contralateral striatal uptake in a number of rest and postural conditions. Conclusion: These data suggest a relationship between Parkinsonian rest tremor and contralateral reduction in striatal dopamine binding. Use of quantitative neurophysiology techniques may allow the demonstration of clinico-pathophysiological relationships in tremor that have remained occult to previous studies. Highlights: We used sensors and TRODAT imaging to examine the relationship between Parkinsonian tremor and the striatum. Parkinsonian tremor correlates with reduced striatal TRODAT uptake contralaterally. This relationship was strongest for rest tremor. Tremor stability index (TSI) also correlated with striatal TRODAT uptake.